First Study of Intra-Arterial Delivery of Myogenic Mononuclear Cells to Skeletal Muscles in Primates. Issue 1 (January 2014) - Skuk, Daniel; Tremblay, Jacques P.
The main challenge of cell transplantation as a treatment of myopathies is the large amount of tissue to treat. Intravascular delivery of cells may be an ideal route if proven to be effective and safe. Given the importance of nonhuman primates for preclinical research in transplantation, we tested the intra-arterial injection of β-galactosidase (β-Gal)-labeled myoblasts in macaques. Cells were injected into one of the femoral arteries in seven monkeys. Some muscle sites were damaged concomitantly in three monkeys. Various organs and muscles were sampled 1 h, 1 day, 12 days, 3 weeks, and 5 weeks after transplantation. Samples were analyzed by histology. Most β-Gal + cells were observed in the capillaries and arterioles of muscles and other tissues of the leg homolateral to the cell injection. Groups of necrotic myofibers in the proximity of an arteriole plugged by a β-Gal + embolus were interpreted as microinfarcts. Scarce β-Gal + cells were observed in the lungs 1 h and 1 day posttransplantation. No β-Gal + cells were observed in other organs or muscles. β-Gal + myofibers were observed 12 days, 3 weeks, and 5 weeks after transplantation in muscles of the leg after the cell injection, in sites that were damaged at the time of cell injection. In conclusion, most intra-arterially injected myoblasts were retained in vessels of the leg homolateral to the cell injection site, and they fused with myofibers in regions in which there was a process of myofiber regeneration. This manuscript is published as part of the International Association of Neurorestoratology (IANR) special issue of Cell Transplantation .